Effect Of Additional Flour Of Moringa Oleifera (Moringa oleifera) On Organoleptic And Chemical Properties Of Tempe Nugget - Exlesia Fininta Sinaga; Tineke M. Langi; Teltje Koapaha (Sam Ratulangi University, 2022)
The purpose of this study was to determine the amount of addition of moringa leaf flour to the panelists' most preferred tempe nuggets, analyze the antioxidant content in the most preferred treatment and analyze the water content, protein content, and fat content. This study used a Completely Randomized Design (CRD) method consisting of five (5) treatments with three (3) replications with the addition of Moringa leaf flour as follows: Treatment A 0.5% moringa leaf flour, Treatment B 1% Moringa leaf flour, Treatment C 1.5% moringa leaf powder, Treatment D 2% moringa leaf powder, Treatment E 2.5% moringa leaf powder. The results obtained showed that the addition of 1.5% Moringa leaf flour was the most preferred by the panelists with the antioxidant activity produced which was classified as strong, namely 99.70 ppm. The value of water content (17%-30%), protein content (17.21%-24.22%), and fat content (1.45%-7.61%).Â Keywords: nuggets, tempeh, moringa leaves.